FRI0289 Denosumab Treatment in Postmenopausal Women with Osteoporosis for Up to 9 Years: Results Through Year 6 of the Freedom Extension. (9th June 2015) - Papapoulos, S.; Roux, C.; Bone, H.G.; Dakin, P.; Czerwiński, E.; Frey, D.; Kendler, D.; Lewiecki, E.M.; Malouf, J.; Mellström, D.; Reginster, J.Y.; Resch, H.; et al.
Abstract : Background: Denosumab treatment was shown to decrease the risk of vertebral and nonvertebral fracture in postmenopausal women with osteoporosis in the 3-year FREEDOM trial. The 7-year FREEDOM Extension is an open-label study to evaluate the long-term safety and efficacy of denosumab treatment for up to 10 years. Objectives: To report the results through year 6 of the FREEDOM open-label Extension, representing up to 9 years of continued denosumab for the treatment of postmenopausal osteoporosis. Methods: During the Extension, all women received 60 mg denosumab every 6 months, and daily calcium and vitamin D. At Extension year 6, bone turnover markers, nonvertebral fracture incidence, and adverse events were evaluated. In these analyses, women in the long-term group received up to 9 years of denosumab (3 years in FREEDOM and up to 6 years in the Extension); women in the cross-over group received up to 6 years of denosumab (3 years of placebo in FREEDOM and up to 6 years of denosumab in the Extension), allowing replication of results from the long-term group. Results: Of the women who enrolled in the Extension, 3, 098 (68%) were still on study at the beginning of year 6, with a mean age of 79 years (range 68–98 years). In both groups, serum CTx and P1NP were similarly reduced after each denosumab dose. The characteristic attenuation was observed through each dosing period and reductions were sustained through Extension year 6. The yearly incidences of nonvertebral (Figure ) and major nonvertebral fractures remained low in both groups. Rates of adverse events and serious adverse events were consistent with previously reported Extension data. In Extension year 6, 2 events were adjudicated positive for ONJ in the cross-over group; there were no cases of atypical femoral fracture in either group. Conclusions: In this aging population, denosumab treatment for up to 9 years maintained reduced bone turnover and was associated with continued low incidence of nonvertebral and major nonvertebral fractures. The benefit/risk profile remained favorable. Disclosure of Interest: S. Papapoulos Consultant for: Amgen Inc., Axsome, Gador, GSK, Merck, Novartis, UCB, C. Roux Grant/research support from: Bongrain, Lilly, MSD, Consultant for: Amgen Inc., MSD, H. G. Bone Grant/research support from: Amgen Inc., Merck, Novartis, Consultant for: Amgen Inc., Merck, Mission, Novartis, P. Dakin Shareholder of: Amgen Inc., Employee of: Amgen Inc., E. Czerwiński Grant/research support from: Amgen Inc., D. Frey Grant/research support from: Abbot, Amgen Inc., Daiichi-Sankyo, Lilly, Novartis, UCB, Consultant for: Amgen Inc., Meda, Takeda, D. Kendler Grant/research support from: Amgen Inc., Astalis, Astra Zeneca, Eli Lilly, GSK, Novartis, Consultant for: Amgen Inc., Eli Lilly, GSK, Merck, Pfizer, Speakers bureau: Amgen Inc., Eli Lilly, Novartis, E. M. Lewiecki Grant/research support from: Amgen Inc., Lilly, Merck, Consultant for: AgNovos, Alexion, Amgen Inc., Lilly, Merck, NPS, Radius Health, J. Malouf: None declared, D. Mellström: None declared, J. Y. Reginster Grant/research support from: Amgen Inc., Bristol Myers Squibb, GlaxoSmithKline, Lilly, Merck Sharp & Dohme, Novartis, Roche, Rottapharm, Servier, Teva, Consultant for: Amgen Inc., GlaxoSmithKline, Lilly, Merckle, Negma, Novartis, NPS, Nycomed, Roche, Servier, Theramex, UCB, Wyeth, H. Resch Grant/research support from: Amgen Inc., Lilly, Consultant for: Amgen Inc., Lilly, MSD, Speakers bureau: Amgen Inc., Lilly, MSD, UCB, N. S. Daizadeh Shareholder of: Amgen Inc., Employee of: Amgen Inc., A. Wang Shareholder of: Amgen Inc., Employee of: Amgen Inc., M. Gavin Shareholder of: Amgen Inc., Employee of: Amgen Inc., R. B. Wagman Shareholder of: Amgen Inc., Employee of: Amgen Inc., M. L. Brandi Grant/research support from: Abiogen, Alexion, Amgen Inc., Bruno Farmaceutici, Eli Lilly, MSD, NPS, Servier, Shire, SPA, Consultant for: Abiogen, Alexion, Amgen Inc., MSD, NPS, Servier, Shire, SPA